Surveying of bench erosion on the Great Hungarian Plain - Kovács, Ferenc; Rakonczai, János; Szatmári, József (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
The degree of soil erosion in the Great Hungarian Plain is far more below the value experienced in hilly areas. However, our investigations also call the attention to the fact that its potentials must not be underestimated. Investigating surfaces with bench erosion gives an opportunity to determine the degree of erosion in plane areas. This unique type of erosion, complemented by gradually increasing aridity, may cause significant changes in the specific formations of saline soils and the vegetation growing in these environments. We have assigned three main measurement methods: 1. field measurement with GPS and geodesic stations; 2. measurements based on fotogrammetric data; 3. transforming and analysing data from different time frames and mapping systems into a uniform system using GIS. Based on the data from the period between 1882 and 2003 from the large area with solonchak soil near the Danube river were large test areas with high degree of erosion selected. In the case of degrading bench ridges an average 10–15 cm/y bench retreat was calculated. The degree of erosion for individual benches compared to the data on the 3rd military survey was 40% in average. Another characteristic feature was the dissection of bench ridges by roads, canals and flock paths leading to the formation of new isolated bench islands. The density of roads, canals and flock paths is getting higher. Erosion becomes more intensive these days in other regions. In the solonetz alkaline type study area of the Trans-Tisza region the degree of erosion is slightly lighter: approximately 0–15 cm/6 years, however, according to the results of field examinations in the last 25 years the soil and vegetation changes due to aridification were highly significant. When analysing a 100 years, a shorter 20 years and the shortest 3 years period during our investigations, that may still require further revisions, the degree of bench erosion was not significant. Based on our experiences so far with evaluating bench erosion, analysing a series of stereo-ortophoto images and field survey with geodesic station in every 3 years may help to eliminate the inaccuracies of the current survey.